Long Noncoding RNA HITTERS Protects Oral Squamous Cell Carcinoma Cells from Endoplasmic Reticulum Stress‐Induced Apoptosis via Promoting MRE11‐RAD50‐NBS1 Complex Formation. Issue 22 (4th October 2020) - Wu, Chenzhou; Chen, Wen; Yu, Fanyuan; Yuan, Yihang; Chen, Yafei; Hurst, Douglas R.; Li, Yi; Li, Longjiang; Liu, Zhe
Abstract: Recent studies have proven that long noncoding RNAs (lncRNAs) exhibit regulatory functions of both DNA damage response (DDR) and endoplasmic reticulum (ER) stress. Herein, ER stress‐induced lncRNA transcriptomic changes are reported in human oral squamous cell carcinoma (OSCC) cells and a novel lncRNA HITTERS ( H ERPUD1 i nt ronic t ranscript of ER s tress) is identified as the most significantly upregulated lncRNA. It is shown that HITTERS is a nucleus‐located lncRNA including two transcript variants. HITTERS lacks an independent promoter but shares the same promoter with HERPUD1 . HITTERS is transcriptionally regulated by Activating Transcription Factor (ATF) 6, ATF4, X‐Box Binding Protein 1 (XBP1), and DNA methylation. In human OSCC tissues, HITTERS is significantly correlated with OSCC clinicopathological features and prognosis. Gain‐ and loss‐of‐function studies reveal that HITTERS promotes OSCC proliferation and invasion via influencing the expression of growth factor receptors and the downstream pathways. Once ER stress is triggered, HITTERS significantly attenuates ER stress‐induced apoptosis both in vivo and in vitro. Mechanically, HITTERS functions as RNA scaffold to promote MRE11‐RAD50‐NBS1 complex formation in the repair of ER stress‐induced DNA damage. To sum up, this study presents a novel lncRNA, namely HITTERS, which links ER stress and DDR together in OSCC. Abstract : HERPUD1 intronic transcript of endoplasmic reticulum (ER) stress ( HITTERS ) is a long noncoding RNA that is regulated by ER stress and protects oral cancer cells from ER stress‐induced apoptosis via promoting DNA repair.